2015
DOI: 10.1111/jgh.13004
|View full text |Cite
|
Sign up to set email alerts
|

Serum diamine oxidase activity as a predictor of gastrointestinal toxicity and malnutrition due to anticancer drugs

Abstract: Serum DAO activity sensitively indicates gastrointestinal damage prior to symptom onset and can be a useful predictor of intestinal mucosal damage and nutritional status in patients receiving chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Yee et al has found that an established first-line treatment for patients in T2DM, metformin, inhibits DAO activity [52]. Previous study also found that serum DAO activity decreased step-by-step significantly during anticancer drug therapy in human, which may be to serve as a useful predictor of gastrointestinal toxicity due to anticancer drug [53]. Our present data found that the levels of DAO also increased significantly in CRC patients, which was correlated with Lactobacillus, Bifidobacterium, and Clostridium cluster I negatively and with F. nucleatum and Enterobacteriaceae positively.…”
Section: Discussionmentioning
confidence: 95%
“…Yee et al has found that an established first-line treatment for patients in T2DM, metformin, inhibits DAO activity [52]. Previous study also found that serum DAO activity decreased step-by-step significantly during anticancer drug therapy in human, which may be to serve as a useful predictor of gastrointestinal toxicity due to anticancer drug [53]. Our present data found that the levels of DAO also increased significantly in CRC patients, which was correlated with Lactobacillus, Bifidobacterium, and Clostridium cluster I negatively and with F. nucleatum and Enterobacteriaceae positively.…”
Section: Discussionmentioning
confidence: 95%
“…Another possible explanation is that Elental could help to maintain mucosal integrity in the gastrointestinal tract, thereby resulting in maintained nutrient absorption. Anticancer drugs, such as 5-fluorouracil, can induce small intestinal mucosal injury and plasma diamine oxidase (DAO) has been reported to be a useful indicator of mucosal injury of the gastrointestinal tract (43). Tanaka et al (7) recently reported that plasma DAO activity was decreased after chemotherapy in patients with esophageal cancer, and patients treated with the Elental diet exhibited a significant increase in DAO activity after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DAO and citrulline, useful early markers in the diagnosis of intestinal mucositis, were both affected by radiation. DAO, which is found primarily in the villus epithelial cells of the small intestine, has been reported to increase in the serum in parallel with the severity of small intestinal mucosal injury induced by anticancer drugs (Miyoshi et al, ) or after radiation exposure (Khayyal et al, ). On the other hand, the serum level of citrulline, a nonprotein amino acid produced exclusively by the enterocytes of the small bowel (Barzał, Szczylik, Rzepecki, Jaworska, & Anuszewska, ), has been shown to decrease secondary to reduction of intestinal functional capacity and impairment of the mucosal barrier as a result of chemotherapy (Herbers, Feuth, Donnelly, & Blijlevens, ) or radiation exposure (Khayyal et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DAO and citrulline, useful early markers in the diagnosis of intestinal mucositis, were both affected by radiation. DAO, which is found primarily in the villus epithelial cells of the small intestine, has been reported to increase in the serum in parallel with the severity of small intestinal mucosal injury induced by anticancer drugs (Miyoshi et al, 2015) or after radiation exposure (Khayyal et al, 2014).…”
Section: Discussionmentioning
confidence: 99%